On the influence of Heat Fluxes on Storms (MAUSAM, 1965)
The influence of eddy fluxes of heat at the interface of the oceans and the atmosphere has been numerically estimated in the case of a North Atlantic cyclone: The role placed by such fluxes is discussed; It is shown that the heat sources and sinks associated with tropospheric features at the earth's surface exert marked influences on the development of mobile pressure systems.